O35. Chromosomal radiosensitivity and genomic instability of Fanconi Anaemia patients in South Africa. (September 2016) - Francies, F.Z.; Baeyens, A.; Wainwright, R.; Poole, J.; Slabbert, J.P.
Abstract : Introduction: Fanconi Anaemia (FA) is an autosomal recessive disorder characterized by defects in DNA repair associated with chromosomal instability and cellular hypersensitivity to DNA cross-linking agents such as mitomycin C (MMC). The clinical manifestation includes congenital and developmental abnormalities and bone marrow failure. FA also has a predisposition to cancer. Fifteen different genetic subtypes of FA have been described. In South Africa, with mixed ethnicity in the population, prevalence of FA ranges between is 1/22 000 for the white Afrikaners to 1/40 000 in the black South Africans. Evidence suggests that FA patients are chromosomally radiosensitive to ionising radiation but with very limited data. The aim of this study is to investigate chromosomal radiosensitivity and genomic instability of homozygous and heterozygous carriers of FA mutations compared to healthy individuals using the micronucleus (MN) assay. Materials and methods: For the G0 MN assay, heparinised blood in culture medium was irradiated at 0 Gy (Baseline), 2 Gy and 4 Gy followed by the immediate stimulation of lymphocytes using phytohaemagglutinin (PHA). Cytochalasin B was added 23 hours later to inhibit cytoplasmic division. Cells were harvested 70 hours later. For the S/G2 MN assay, we used the same radiation doses but the culture was only irradiated 72 hours after addition of PHA. To detect DNA damage in the S/G2 phase of the cell cycle, the cells were harvested 8 hours post irradiation. The third assay is similar as the G0 MN assay except the cell damage is induced using MMC. All slides were stained with acridine orange and micronuclei were scored using a fluorescent microscope. Results: The micronuclei frequencies are higher in the homozygous carriers compared to the heterozygous carriers and healthy individuals. Conclusions: FA mutation carriers show higher chromosomal radiosensitivity and genomic instability compared to healthy individuals.